2021
DOI: 10.3390/biology10080713
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sexual Behavior and Demographic Characteristics in the Expression of HPV-Related Biomarkers in a Colposcopy Population of Reproductive Age Greek Women

Abstract: Despite the significant scientific evolution in primary and secondary cervical cancer prevention in the battle started by George Papanicolaou in the previous century, global cervical cancer mortality rates remain disappointing. The widespread implementation of HPV-related molecular markers has paved the way to tremendous developments in cervical cancer screening, with the transition from cytological approach to the more accurate and cost-effective HPV testing modalities. However, the academic audience and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
2
12
0
3
Order By: Relevance
“…This evidence-based advice for the postoperative period is currently adopted by most departments worldwide. From this perspective, consistent condom use will serve both purposes (family planning as well as protection against HPV) [ 25 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence-based advice for the postoperative period is currently adopted by most departments worldwide. From this perspective, consistent condom use will serve both purposes (family planning as well as protection against HPV) [ 25 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV vaccination rates were low at the time the study started to recruit; there was also no evidence of the potential role of vaccination following conization in preventing recurrence [ 25 , 60 ]. Of note is that our group has previously illustrated a beneficial contribution of HPV vaccination affecting untreated patients with mild dysplasias under colposcopic surveillance [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge, together with the knowledge of HPV as the most common STI, could improve the HPV infection spread [ 55 ]. However, very few studies have reported the association between knowledge of STI and sexual behavior and HPV status [ 56 , 57 ]. Thus, more research on HPV infection and HPV vaccine knowledge, behavior, and attitudes is required.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal HPVs are typically contracted through coital or non-coital sexual contact, with non-sexual transmission still disputed [29]. The most recent data suggest that almost all sexually active individuals have been or will be infected with at least one type of genital HPV [30,31]. The International Agency on Research on Cancer (IARC) has categorized HPVs into HR and LR, with HR types being capable of promoting precancerous and cancerous lesions in affected individuals [32].…”
Section: Mucosal Hpvmentioning
confidence: 99%